Is uptake of disability-related social security benefits modified by demographic, social and area-level factors? - O'Reilly, Dermot; Rosato, Michael; Maguire, Aideen (International Journal of Population Data Science, 2018)
Introduction In the UK Disability Living Allowance (DLA) provided a non means-tested contribution towards the disability-related costs of living for disabled people aged Objectives and Approach Three 2011 census-based measures of self-reported health (number of chronic disabilities; activity limitation (a little; a lot); and chronic poor mental health) were linked to 2011 DLA records. Census returns provided individual demographic, socio-economic, social and area-level characteristics. Overall, 92.5% of DLA records were matched to 1.4 million Census records. Results Interim analysis analyses confirms health as the main determinant of DLA uptake, but that for a given level of health, uptake was… higher amongst non-married and those of lower socio-economic status ( OR 1.76; (95%CI 1.68, 1.84) most deprived vs. least deprived), lower amongst ethnic minorities (OR 0.87 (95%CIs 0.78, 0.97) non-white vs. white), migrants (OR 0.37; (95%CI 0.34, 0.39) migrants vs. non migrants) and slightly lower in rural communities (OR 0.95; (95%CI 0.93, 0.97) rural vs. urban). Conclusion/Implications Poor health is the predominant determinant of disability benefits uptake but other social and socioeconomic factors are influential. Results of these analyses might assist in better targeting of benefits.